Correction: Russians are the fastest 100-km ultra-marathoners in the world. - Beat Knechtle; Pantelis Theodoros Nikolaidis; Fabio Valeri (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0199701.].